THE CHALLENGES OF REGIONAL INTEGRATION IN AFRICA - Jailson E. da G.R. Gomes (European Scientific Journal, ESJ, 2014)
After the World War II mankind entered a new phase of international relations development. It is characterized by extension of international economic, political and cultural collaboration; intensification of internationalization and globalization processes, further more world community tends to greater integration, greater foreseeability, and growth of organization and development control mechanisms. In this job the accent is laid upon analyses of regional integration, which is one of the key methods of solving globalization challenges. Before dwelling upon integration in Africa, it is necessary to define the notion of integration and globalization, analyze the way they intercourse and trace the way globalization process influences the integration process in Africa.